Analyzing the impact of aging populations on healthcare system sustainability - Shrivastava, Pranjul; Syed Sabir Ali, Syed Sajid Ali (Journal of Neonatal Surgery, 2025)
An international phenomenon, the aging population presents serious problems for healthcare systems. Increased demand for healthcare services, long-term care, and chronic disease management results from the growing proportion of elderly people brought on by rising life expectancy and falling birth rates. The workforce, financial resources, and infrastructure of the healthcare industry are all severely strained by this demographic change. With a focus on important topics like healthcare costs, labor shortages, and the requirement for policy changes, this study attempts to examine how aging populations affect the sustainability of healthcare systems. The study highlights the opportunities and problems brought about by an aging population by reviewing case studies and trends from around the world. The results underscore the significance of creative approaches, including integrated care models, digital health technologies, and policy changes, in guaranteeing the viability of healthcare systems amidst demographic shifts.